Evaluation of acoustical parameters of a Brazilian popular housing model - Ferreira, Technical Notes - J. A.; Diniz, F. B.; Ferreira, A.; Zannin, P.H. T. (Archives of Acoustics, 2004)
The present survey shows the results obtained from the evaluation of the acoustical parameters in situ, through standardized measurements, inside a popular residence designed to offer an option to combat the housing deficit of the low income Brazilian population.